Effects of Reducing Nitrogen Fertilizer Combined with Microbial Agent Application on Flue-cured Tobacco Yield and Soil Microbial Diversity - Chunyi WU; Shasha LUO; Ting YANG; Yinglin LU; Ruimin HE; Yue NIU; Xiaoli ZHANG; Yuxing AN (Guangdong nongye kexue, 2023)
【Objective】The study aims to explore the effects of reducing nitrogen fertilizer combined with microbial agent application on flue-cured tobacco yield and soil microbial diversity.【Method】Using Yunyan 87 as the experimental material, four treatments were set up: T1 local conventional fertilization(CK), T2 conventional fertilization + microbial agent, T3 conventional fertilization + 10% reduction of nitrogen fertilizer+ microbial agent, and T4 conventional fertilization + 20% reduction of nitrogen fertilizer + microbial agent. The agronomic traits of flue-cured tobacco at different stages, the economic traits of flue-cured tobacco leaves, and the diversity of rhizosphere soil microbial communities at maturity were measured for each treatment.【Result】There was no significant difference in the agronomic traits of flue-cured tobacco among different treatments and periods. This indicates that nitrogen reduction treatment did not affect the growth of flue-cured tobacco. The economic traits of flue-cured tobacco among different treatments showed no significant difference in the output value of T2 and T3 treatments compared to T1 treatment. The output value of T4 treatment was 1 351.56 yuan/667 m2, which was a significant difference compared to T2 treatment. Compared with T1 treatment, there was no significant difference in soil physicochemical properties or indicators among different treatments. (2) Each treatment with microbial agents increased the total and unique OTUs of bacteria and fungi. Compared to T1 treatment, the T2 treatment increased the unique OTUs of bacteria by 68.4%, the total OTUs of fungi treated with T2 and T3 increased by 60.2% and 54.9%, respectively, T2 and T3 increased the unique OTUs of fungi by 85.2% and 78.2%, respectively, as well as the fungal richness (Chao index) of T2 and T3 treatments. (3) At the phylum level, the relative abundance of Proteobacteria in T4 treatment was significantly higher than that in other treatments, and there was no significant difference in the level of fungi under different treatments. (4) The relative abundance of s_Fusarium_equiseti in T1 treatment was higher than that in other treatments. T4 treatment increased the number of beneficial microorganisms, such as c_Alphaproteobacteria, o_Sphingosine, g_Gemmatimonas, and c_Bacteroidota, significantly.【Conclusion】The combination of microbial agents and a moderate reduction of nitrogen fertilizer application (10%) increased the output value of flue-cured tobacco by 12.5% compared to conventional fertilization, while also improving the composition of soil microbial communities.